Postural drainage in intubated patients with acute lobar atelectasis - A pilot study - M. W. Krause; H. Van Aswegen; E. H. De Wet; G. Joubert (AOSIS, 2000)
Objectives: The movement and mobilisation of an intubated patient in the intensive care unit is restricted by the presence of various drains and intravenous lines. Difficulty to position the patient in the correct postural drainage positions, often leads physiotherapists to using modified postural drainage positions to mobilise secretions. A comparison of effectiveness between the correct postural drainage positions and the modified postural drainage positions during the treatment of acute lobar atelectasis in the intubated patient was conducted. Subjects: Intubated men and women between the ages of 13 and 85 years in the intensive care units of Pelonomi and Universitas Hospitals in Bloemfontein diagnosed with acute lobar atelectasis of the lower lobes were considered for inclusion in this pilot study. Intervention: A controlled randomised clinical experiment was conducted. Group A received inhalation therapy whilst placed in a postural drainage position for 15 minutes. Thereafter percussion was done for five minutes followed by a sterile suction procedure. Group B received the same treatment but modified postural drainage positions were used. Both groups received treatment twice daily. Results: On average, group A required three treatments and nil follow-up chest X-rays before the collapse was resolved, as opposed to the average of 4.5 treatments and one follow-up chest X-ray required by group B before the same result was obtained. In group A the oxygenation compared to Group B was improved. The findings were not statistically significant. Conclusion: The use of postural drainage positions in intensive care suggests quicker resolution of acute lobar atelectasis and improves oxygenation.